Genetic Diversity and Health Properties of Polyphenols in Potato - Haroon Rasheed; Daraz Ahmad; Jinsong Bao (Antioxidants, 2022)
Polyphenol is one of the most essential phytochemicals with various health benefits. Potato (Solanum tuberosum L.) is known as a potential source of polyphenols, and also has health benefits in which phenolic acids, such as chlorogenic, ferulic acid, caffeic acid, and flavonoids, such as anthocyanins, sustainably play the most significant role. Almost every polyphenol contributes to various biological activities. In this review, we collected comprehensive information concerning the diversity of polyphenols in potatoes, and the effects of post-harvest processing and different cooking methods on the bioavailability of polyphenols. To achieve maximum health benefits, the selection of potato cultivars is necessary by choosing their colors, but various cooking methods are also very important in obtaining the maximum concentration of polyphenolic compounds. The health properties including major biological activities of polyphenols, such as antioxidant activity, anticarcinogenic activity, anti-inflammatory activity, anti-obesity activity, and antidiabetic activity, have also been summarized. All these biological activities of polyphenols in potatoes might be helpful for breeders in the design of new varieties with many health benefits, and are expected to play a vital role in both pharmaceutical and nutraceutical industries.